Agricultura familiar, assistência técnica e extens\~ao rural e a política nacional de Ater - César Nunes de Castro; Caroline Nascimento Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– In Brazil, the Technical Assistance and Rural Extension services originated in the late 1940s, when the Association of Credit and Rural Assistance was created in the state of Minas Gerais in 1948. The purpose of this work is to analyze the evolution of such service in Brazil since its creation and its relation with family agriculture, culminating with considerations about the recent National Policy of Technical Assistance and Rural Extension (Pnater). For this, a brief history of rural extension in Brazil is presented, as well as a summary of the current situation of this service in the country and the discussion about the reformulation of the public rural extension service, main service provider for family farmers. The actual construction of this new public system is still almost entirely to be done. To rebuild at least part of its capacity and to build partnerships with non-state entities for this purpose, while incorporating new concepts into the process, is not a trivial task. There are doubts about the state's capacity to conduct this work, as well as the results that will be obtained from this.
Keywords: Q1; Q16; Q18; 330; family farming; technical assistance; rural extension; National Technical Assistance and Rural Extension Policy